How Relevant Are the Best Practice Projects as Strategy for Knowledge Management? Case Study of Best Practice on Social Rights Database of Barcelona City Council - Barbieri Muttis, Nicolás; Fierro Fidalgo, Yolanda (Revista del CLAD Reforma y Democracia, 2019)
Best practice databases have spread as part of the knowledge management strategies in public administration. However, research on its objectives, methodologies and impacts is still scarce. What potential and challenges does these initiatives have when trying to revalue the professionals’ knowledge and their participation? What kind of results and impact do they have? This paper builds a guide to answer these questions, identifying three key dimensions for the analysis of good-practice databases: 1) the methodology, 2) the communication of its results and 3) the impact on the people responsible for the practices. The article applies this guide to the analysis of the Best Practice on Social Rights Database of Barcelona City Council and identifies key aspects. Regarding the methodology, reliability and suitability of the practices included in the databases is still a challenge. However, there are mechanisms to ensure rigorous analysis and avoid distrust in best practices databases. Regarding the communication of results, knowledge transferability cannot be taken for granted. The kind of information to communicate is a key factor: the more contextualized and realistic (no only emphasizing positive aspects) the information is, the more possibilities of being transferred will exist. Finally, regarding the assessment and the impact of the best practice databases, this document identifies some strategies of what has been called second generation of knowledge management. It is essential to design specific mechanisms so that the best practices databases can have an impact on the learning, particularly in relation to the group of professionals involved.
Keywords: Public Management; Best Practices; Knowledge Management; Social Programs; Case Analysis; España